Does Short-Term International Immersion have a Sustainable Impact on Teachers’ Cultural Competence? Follow-up Interviews Eight Years After a Teaching Experience in South Korea - Kevin Oh (Indiana University Office of Scholarly Publishing, 2021)
This qualitative study was conducted with teacher candidates studying in a Masters program at a university on the west coast in the United States. The main goal was to capture if immersion in a foreign culture and the short-term teaching of primary and secondary school students in South Korea had any sustainable impact on the participating teachers’ perception of their cultural knowledge, competence, and awareness almost a decade after their immersion experience. The researchers interviewed four teachers who had participated in one of two immersion projects conducted in 2010 and 2011. A questionnaire on teachers’ self-efficacy regarding culturally responsive teaching (modified from Chu & Garcia, 2014) was administered prior to the interview giving the participants a tool to reflect on what it means to be a culturally responsive teacher and to self-assess their own cultural competence and teaching practices. Four themes emerged from the interviews, namely, perspective-taking ability, relationships, teaching strategies, and cultural knowledge. The findings indicate that international immersion not only offers an effective way for pre-service teachers to receive intercultural training. It also has the potential to create transformative learning experiences by immersing students in cultural contexts unfamiliar to them. The findings from this study will be interesting to teacher educators who consider integrating international immersion projects into their teacher education programs.